Layered porous organic composite membrane for organic solvent system, preparation method and application
Porous flexible polymer nanosheets were prepared by using two-dimensional hard templates in an organic solvent system, and combined with the characteristics of Dopa and PPD, porous flexible polymer nanosheets were prepared, which solved the problem of insufficient stability and selectivity of traditional membrane materials in the organic solvent system, and achieved efficient solvent penetration and retention properties.
Patent Information
- Application Number
- CN202411943254.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
It is difficult to develop film materials that are both stable and highly selective in the prior art. Especially in organic solvent systems, traditional inorganic film materials have problems such as poor elasticity, brittle material, and unresistance in shear, while polymer film materials have problems such as poor stability and low permeability such as solvent dissolution and swelling.
Polymer nanosheets were prepared by using a two-dimensional hard template strategy, combined with the characteristics of Dopa self-polymerization and PPD co-deposition, porous flexible polymer nanosheets with the characteristics of polymer and inorganic nanosheets were prepared, and a layered porous organic composite membrane was prepared by vacuum suction filtration.
Excellent solvent permeability and high retention properties of the membrane in the organic solvent system are achieved, while good stability and repeatability are also achieved.
Smart Images

Figure CN119793224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous organic materials and organic solvent nanofiltration, and in particular to a layered porous organic composite membrane for an organic solvent system, a preparation method and application thereof in the organic solvent system. Background Art
[0002] Compared with traditional separation technologies such as distillation, absorption, and adsorption, membrane separation technology has the advantages of low energy consumption, green efficiency, and high economic benefits. Organic solvent nanofiltration, as an emerging membrane separation technology, has been widely used in the fields of medicine and chemical industry. The use of this technology to achieve solute extraction, solvent purification, and organic solvent separation and recycling is an important means of energy conservation and environmental protection, and it has important scientific significance and research value. In the precise separation process of organic solvent systems, the separation membrane is usually composed of a base support layer and a precise selection layer. The selection layer membrane material is the core of membrane technology. Although the organic solvent system separation membrane was proposed in the early 1970s, it has almost no large-scale application so far. The main reason is that it is difficult to develop a membrane material that is both stable and highly selective. Membrane materials are mainly inorganic membrane materials and polymer membrane materials. Separation membranes prepared from inorganic materials have good separation performance, especially layered membranes prepared from inorganic nanosheets have high separation performance, high temperature resistance and good chemical stability, but they have problems such as poor elasticity, brittle materials, and shear resistance. In addition to inorganic materials, the rapid development of polymer materials provides excellent material selection for the preparation of solvent-resistant separation membranes. Polymer materials have the advantages of solvent resistance and strong operability due to their strong structural designability. However, most polymer materials have poor stability such as solvent dissolution and swelling and low permeability. Making organic polymer materials into porous structures can effectively improve the problem of low permeability of polymer membranes, but the preparation of porous polymers is highly challenging and it is difficult to maintain their toughness and film-forming properties. Therefore, a two-dimensional layered porous organic composite membrane is prepared, and the interlocking structure formed by the stacking of porous organic nanosheets can combine the unique advantages of porous polymer membrane materials and inorganic two-dimensional membrane materials, providing new ideas for the development and application of membranes in organic solvent systems.
[0003] Faced with global issues such as energy resource constraints and environmental risk challenges, there is an urgent need to change traditional energy-intensive separation technologies, develop sustainable and low-energy separation methods, and promote green transformation and upgrading of the industry. Membrane separation technology has been applied on a large scale in wastewater treatment, and the development of membrane separation technology that can be used in organic solvent systems has become a research hotspot. Summary of the invention
[0004] The purpose of the present invention is to provide a layered porous organic composite membrane for an organic solvent system, a preparation method and an application thereof, wherein the polymer nanosheet is an organic porous nanomaterial, and the prepared composite membrane exhibits excellent solvent permeability and high interception performance as a conventional nanofiltration membrane. The preparation process is repeatable.
[0005] The present invention provides a layered porous organic composite membrane for an organic solvent system, wherein the layered porous organic composite membrane has a typical layered stacking structure and a porous structure, a membrane thickness of 0.5 to 1.5 μm, and a specific surface area of 35 to 45 m 2 / g, and the minimum pore size is 1.2nm.
[0006] The present invention also provides a method for preparing a layered porous organic composite membrane for an organic solvent system, the specific steps of which are as follows:
[0007] S1, prepare a two-dimensional nanosheet hard template dispersion and adjust the pH of the dispersion; take a certain amount of nickel nitrate hexahydrate and urea in a molar ratio of 1:4 and add them to water, stir until they are completely dissolved, then add ethylene glycol, and wait for the solution to be mixed until the components are uniform for use. Place the prepared solution in a microwave reactor, centrifuge and wash to collect the precipitate after the reaction, vacuum dry it, grind it into a solid powder using a mortar, ultrasonically disperse it in an aqueous solution, let it stand, take the supernatant, and adjust it to 8.5 using Tris and hydrochloric acid solution.
[0008] Preferably, the nickel hydroxide nanosheets prepared by the above method are referenced at: DOI: 10.1038 / srep05787
[0009] Preferably, in the above method, the volume ratio of water to ethylene glycol is 7:1, the power of the microwave reactor is 700w, the reaction time is 3-5min, and the centrifuge speed is 4000-5000r / min.
[0010] Preferably, the concentration of Tris solution used to adjust the pH value in the above method is 0.01 mol / L.
[0011] S2, adding the polymer monomer to the hard template dispersion to make it fully adhere to the hard template surface;
[0012] A certain amount of Dopa or Dopa & PPD is added to the above nanosheet dispersion, and the reaction is stopped after stirring for a period of time, and the precipitate is centrifuged and collected to remove excess and residual polymer monomers or oligomers. At this time, the precipitate is Dopa@Ni(OH)2 or Dopa&PPD@Ni(OH)2 hybrid nanosheets.
[0013] Preferably, the solubility of Dopa is 0.1-0.2 g / L, the ratio of Dopa to PPD during co-deposition is 1:1-1:3, the reaction time is 60-120 min, and the centrifuge speed is 4000-5000 r / min.
[0014] S3, using acid etching to obtain a polymer nanosheet dispersion, centrifugally washing and dispersing it into an aqueous solution;
[0015] After the hybrid nanosheets are evenly dispersed in deionized water by ultrasonic, an acid solution is added for etching. After a period of reaction, the acid solution is removed by centrifugation for multiple times to obtain polymer nanosheets.
[0016] Preferably, the acid solution is 0.1 mol / L hydrochloric acid or saturated ethylenediaminetetraacetic acid (EDTA) solution.
[0017] Preferably, the etching time is 4 to 5 hours, and the centrifuge speed is 7000 to 8000 r / min.
[0018] S4, diluting the nanosheet solution and using a vacuum filtration method to prepare a layered porous organic composite membrane.
[0019] Specifically, when vacuum filtration is used to extract the membrane, the nanosheet dispersion is first allowed to stand by gravity sedimentation, then 0.1 bar pressure is added to extract the membrane, and finally 1 bar pressure is added to filter and form the membrane when the solution is 100 mL.
[0020] S5, the membrane prepared by vacuum filtration method was stored at 15°C for 24 h and allowed to stand at room temperature for 24 h for use.
[0021] The layered porous organic composite membrane of the invention is used for nanofiltration of organic solvents.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0023] 1) The present invention uses a two-dimensional hard template strategy to prepare polymer nanosheets. First, Ni(OH)2 nanosheets are prepared. The self-polymerization characteristics of Dopa are used to make it evenly attached to the hard template and then etched to obtain a porous flexible polymer nanosheet with the characteristics of both high molecular polymers and inorganic nanosheets. A polymer two-dimensional composite membrane is prepared by a vacuum filtration method. At the same time, Dopa can undergo Michael addition reaction, and adding PPD co-deposition as a porogen can improve the permeability and selectivity of the membrane.
[0024] 2) The layered porous organic composite membrane of the present invention has a simple preparation method, low raw material price, simple and mild operating conditions, and has good solvent permeability and solvent retention performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a surface scanning electron microscope image of the Dopa nanosheet obtained in Example 1;
[0026] Figure 2 This is an atomic force microscope image of the surface of the Dopa two-dimensional composite film obtained in Example 1;
[0027] Figure 3 This is a cross-sectional scanning electron microscope image of the Dopa two-dimensional composite membrane obtained in Example 1;
[0028] Figure 4 This is the pore size distribution diagram of the Dopa two-dimensional selective layer obtained in Example 1.
[0029] Figure 5 This is an atomic force microscope image of the Dopa@PPD nanosheet obtained in Example 2;
[0030] Figure 6 This is an atomic force microscope image of the Dopa@PPD two-dimensional composite film surface obtained in Example 2;
[0031] Figure 7 This is a cross-sectional scanning electron microscope image of the Dopa@PPD two-dimensional composite film obtained in Example 2;
[0032] Figure 8 This is the pore size distribution diagram of the Dopa@PPD two-dimensional selective layer obtained in Example 2.
[0033] Fig. 9 The nitrogen adsorption analysis isotherm diagram of the two-dimensional composite membrane obtained in Examples 1 and 2.
[0034] Fig.10 The nitrogen adsorption analysis isotherm diagram of the composite membrane obtained in Comparative Examples 1 and 2.
[0035] Fig.11 The solvent permeation performance and dye retention performance of the membranes were obtained for Examples 1, 2 and Comparative Examples 1, 2, 3. DETAILED DESCRIPTION
[0036] The present invention will be further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0037] All raw materials of the present invention are not particularly limited in their sources and are purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0038] The devices involved in the present invention are not particularly limited to devices commonly used in the art, and those skilled in the art are familiar with their operation and use methods.
[0039] Example 1
[0040] Preparation of Ni(OH)2 template: Add 30ml of deionized water to a 250ml beaker, take a certain amount of nickel nitrate hexahydrate and urea in a molar ratio of 1:4 and add them to the water, stir to completely dissolve, then add 210ml of ethylene glycol, and wait for the solution to be mixed until the components are uniform for use. Place the prepared solution in a microwave reactor, microwave heat for 4 minutes at 100% power, take it out and cool it naturally to room temperature, collect the precipitate by centrifugation at a speed of 3500rpm, then use anhydrous ethanol and deionized water to centrifuge and wash twice each, vacuum dry it at 90℃ for 24h, take it out, and grind it into solid powder in a mortar for use.
[0041] Preparation of Dopa two-dimensional nanosheets: Add 1000ml of deionized water to a beaker, take 1.21g of Tris and add it to the water, stir to completely dissolve it, and fine-tune the solution to a pH of 8.5. Take 0.2g of Ni(OH)2 nanosheets and add them to the prepared Tris solution, ultrasonicate for 40min to disperse it evenly, let it stand for 3-4h, take 500ml of the upper solution, heat and stir in a 25℃ water bath, take 0.5g of Dopa and add it to the above nanosheet dispersion, stop the reaction after 1h, collect the precipitate by centrifugation, and use Tris solution to centrifuge and wash the precipitate to remove excess and residual Dopa. At this time, the precipitate is Dopa@Ni(OH)2 hybrid nanosheets, which are etched with 0.1mol hydrochloric acid solution, and then centrifuged and washed 3 times with deionized water at 8000rpm to obtain Dopa two-dimensional porous nanosheets.
[0042] Preparation of Dopa composite membrane: Disperse the above-mentioned nanosheets into a certain amount of deionized water, and disperse them evenly by slight ultrasound. Then, take a certain amount of Dopa nanosheet dispersion and add it to the filtration device. Use the reduced pressure filtration method to prepare the Dopa thin film composite membrane from bottom to top. After the dispersion is evacuated, wait for 5 minutes to remove the membrane, refrigerate it at 15°C for 24 hours, and then dry it at room temperature for 24 hours for use.
[0043] The nanofiltration performance test of the solvent is performed as follows:
[0044] The sample membrane is installed in the dead-end test device, 50 mL of the solvent to be tested is added, and the driving force is controlled by adjusting the N2 pressure reducing valve. After the permeate flows out stably, a certain amount of solvent is taken, the volume of the solvent taken is read, and the absorbance of the solution before and after passing through the membrane is measured using a UV-visible spectrophotometer. In this process, in order to avoid errors caused by solvent volatilization, the solvent is always under the protection of liquid nitrogen.
[0045] The permeability coefficient of a solvent refers to the volume of the solvent that permeates the membrane per unit area, unit time, and unit pressure. The calculation formula is as follows:
[0046]
[0047] Where:
[0048] Permeance——Permeability coefficient of solvent, Lm -2 h -1 bar -1 ;
[0049] V——volume of solvent permeating through the membrane, L;
[0050] A——Effective test area of membrane, m 2 ;
[0051] t——test time, h;
[0052] p——applied pressure, bar;
[0053] Dye retention rate test The dye retention rate is the percentage of dye molecules retained in the raw material. After the flux reaches stability, take 10mL of sample, and then test the concentration of the original solution and the permeate by UV spectrophotometer. The dye retention rate of the membrane is calculated by the following formula:
[0054]
[0055] Where: R is the interception rate; C P is the permeate concentration; C F is the original solution concentration.
[0056] The results showed that the methanol flux of Dopa two-dimensional layered membrane was 79.1 Lm -2 h -1 bar -1 , the retention rate of reactive black (RB) is 95.2%.
[0057] Example 2
[0058] Preparation of Ni(OH)2 template: Add 15ml deionized water to a 125ml beaker, take a certain amount of nickel nitrate hexahydrate and urea in a molar ratio of 1:4 and add them to the water. Stir to completely dissolve them and then add 105ml ethylene glycol. Mix the solution until the components are uniform and set aside. Place the prepared solution in a microwave reactor, heat it with a microwave at 80% power for 5 minutes, take it out and cool it naturally to room temperature, collect the precipitate by centrifugation at 4000rpm, then use anhydrous ethanol and deionized water to centrifuge and wash twice each, vacuum dry it at 120℃ for 24h, take it out, and grind it into solid powder in a mortar for use.
[0059] Preparation of Dopa&PPD two-dimensional nanosheets: Add 1000ml of deionized water to a beaker, add 1.21g of Tris to the water, stir to completely dissolve it, and fine-tune the solution to a pH of 8.5. Take 0.3g of Ni(OH)2 nanosheets and add them to the prepared Tris solution, ultrasonicate for 50min to disperse it evenly, let it stand for 12h, take 800ml of the upper solution, heat and stir in a 25℃ water bath, take 0.8g of Dopa and 0.4g of PPD and add them to the above nanosheet dispersion, stop the reaction after 2h, collect the precipitate by centrifugation, and use Tris solution to centrifuge and wash the precipitate to remove excess and residual Dopa and PPD. At this time, the precipitate is Dopa&PPD@α-Ni(OH)2 hybrid nanosheets, which are etched with a saturated EDTA solution, and then centrifuged and washed 3 times with deionized water at 8000rpm to obtain Dopa&PPD two-dimensional porous nanosheets.
[0060] Preparation of Dopa&PPD composite membrane: Disperse the above-mentioned nanosheets into a certain amount of deionized water, and disperse them evenly by slight ultrasound. Then, take a certain amount of Dopa&PPD nanosheet dispersion and add it to the filtration device. Use the reduced pressure filtration method to prepare the Dopa&PPD thin film composite membrane from bottom to top. After the dispersion is evacuated, wait for 5 minutes and remove the membrane. Refrigerate it at 15°C for 24 hours, and then dry it at room temperature for 24 hours for use.
[0061] The nanofiltration performance test was carried out using the same testing device and method as in Example 1.
[0062] The results showed that the methanol flux of Dopa&PPD two-dimensional layered membrane was 128.2Lm -2 h -1 bar -1 , the retention rate of reactive black (RB) is 91.5%.
[0063] Comparative Example 1
[0064] Preparation of Dopa@PES composite membrane: Soak the commercial polyethersulfone membrane (UE050) with a molecular weight cutoff of 50,000 in deionized water for 12 hours, prepare 1L of Tris solution with a concentration of 0.01mol / L in a beaker, fine-tune the pH to 8.5, put the treated PES commercial membrane into the beaker, add 1g Dopa and shake it at 25°C for 24 hours, so that Dopa is uniformly deposited on the surface of the PES membrane to form a selective layer. Then take out the membrane, rinse the surface with deionized water, and put it in a 35°C forced air drying oven to dry for use.
[0065] The results showed that the methanol flux of Dopa@PES composite membrane was 6.2 Lm -2 h -1 bar -1, the retention rate of reactive black (RB) is 59.6%.
[0066] Comparative Example 2
[0067] Preparation of Dopa&PPD@PES composite membrane: Soak the commercial polyethersulfone membrane (UE050) with a molecular weight cutoff of 50,000 in deionized water for 12 hours, prepare 1L of Tris solution with a concentration of 0.01mol / L in a beaker, fine-tune the pH to 8.5, put the treated PES commercial membrane into the beaker, add 1g Dopa and 0.5g PPD, and react on a shaker at 25°C for 24 hours, so that Dopa and PPD are uniformly deposited on the surface of the PES membrane to form a selective layer. Then take out the membrane, rinse the surface with deionized water, and put it in a 35°C forced air drying oven to dry for use.
[0068] The results showed that the methanol flux of Dopa&PPD@PES composite membrane was 12.9Lm -2 h -1 bar -1 , the retention rate of reactive black (RB) is 55.4%.
[0069] Comparative Example 3
[0070] Preparation of GO layered membrane: The peeled GO nanosheets were diluted into deionized water, and the tested concentration was 0.5 g / L. 300 μL of GO solution was dispersed in 200 mL of deionized water. Ultrasonication was performed for 40 min to evenly disperse the nanosheets into the aqueous solution. The GO layered membrane was prepared by vacuum filtration and dried in a 60°C forced air drying oven for later use.
[0071] The results showed that the methanol flux of the GO layered membrane was 18.5 L m -2 h -1 bar -1 , the retention rate of reactive black (RB) is 65.8%.
[0072] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A layered porous organic composite membrane for an organic solvent system, characterized in that: The layered porous organic composite membrane has a typical layered stacking structure and a porous structure, a membrane thickness of 0.5 to 1.5 μm, and a specific surface area of 35 to 45 m 2 / g, and the minimum pore size is 1.2nm.
2. The method for preparing the layered porous organic composite membrane according to claim 1, comprising the following steps: S1, preparing a two-dimensional nanosheet hard template dispersion and adjusting the pH of the dispersion; S2, adding polymer monomers to the hard template dispersion, so that the polymer monomers are fully attached to the surface of the hard template, and the polymer monomers are uniformly polymerized and deposited on the hard template to obtain hybrid nanosheets; S3, etching the hybrid nanosheets using acid to obtain a polymer nanosheet dispersion; S4, diluting the polymer nanosheet dispersion and preparing a layered porous organic composite membrane by vacuum filtration; S5, the membrane prepared by vacuum filtration method was stored at 15°C for 24 h and allowed to stand at room temperature for 24 h for use.
3. The preparation method according to claim 2, characterized in that: The two-dimensional nanosheet hard template in step S1 is a metal hydroxide or a metal oxide, and the polymer monomer in step S2 is levodopa or levodopa and p-phenylenediamine.
4. The preparation method according to claim 3, characterized in that: The two-dimensional nanosheet hard template in step S1 is nickel hydroxide.
5. The method according to claim 2, characterized in that: In the step S1, the pH value of the hard template dispersion is adjusted by tris(hydroxymethyl)aminomethane and hydrochloric acid.
6. The method according to claim 2, characterized in that: In step S2, the polymer monomer concentration is 0.1-0.2 mg / mL, and the reaction temperature is 25°C.
7. The method according to claim 2, characterized in that: In S3, the pH value of the etching solution is between 1 and 2, and the temperature is between 25°C and 30°C.
8. The use of the layered porous organic composite membrane according to claim 1, characterized in that: Used for nanofiltration of organic solvents.
Citation Information
Patent Citations
An organic solvent nanofiltration composite membrane adopting molybdenum disulfide as an activated layer and a preparing method thereof
CN108993168A
Universal preparation method of reduced graphene oxide-based asymmetric composite membrane
CN112439322A
Dual-regulation two-dimensional MXene composite membrane and preparation method thereof
CN115041027A
Mixed matrix membrane doped with molybdenum disulfide nanosheet modified material as well as preparation method and application of mixed matrix membrane
CN115253714A
Preparation method and application of amine polymer and transition metal sulfide self-assembled porous nanofiltration membrane
CN115445447A